POLA KOMUNIKASI KEPEMIMPINAN DALAM MENINGKATKAN KINERJA PEGAWAI DI BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA KABUPATEN PELALAWAN - Rayani Afrianty; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The communication system of leadership is the issues that occur in The Society’s Empowerment and Governance Countryside Pelalawan District office in order to increasing performance of employees. The purpose of this research is to find out how do the communication system of leadership in increasing performace of employees of the Society’s Empowerment and Governance Countryside Pelalawan District, then to find out media that are used in increasing performance of employees.This research used qualitative descriptive method by using purposive sampling. The informant is selected based on the specific characteristic. The researcher chooses 5 peoples based on their employment status. Collection of the data is done by using observation, interview, and documentation.The result of this research showed that the communication system of leadership in The Society’s Empowerment and Governance Countryside Pelalawan District is very involved in increasing performance of employees of The Society’s Empowerment and Governance Countryside Pelalawan District. The leadership could establish the communication as well fromhead to underling so the instruction of leadership delivered clearly and the employees could responsible toward their job . The media that is used in increasing performance employees is by discussion, phoning and morning ceremonial.Keywords: The Communication System, Leadership, Media, Performance of Employees.